(untitled) (Research, Society and Development, 2022)
The objective is to show the contributions of the meteorological elements of the municipality of Matinhas, aiming at sustainable development in the productive areas of citrus, fruit and family farming. The meteorological elements studied were: maximum, average, minimum temperature and air thermal amplitude, relative air humidity, wind (intensity and direction), total insolation, cloud cover, evaporation, reference evapotranspiration, precipitation. The rainfall data corresponded to the 2000-2018 series, provided by the Executive Agency for Water Management of the State of Paraíba. The average temperature fluctuates between 22 °C to 25.2 °C, the maximum temperature fluctuates from 27.3 °C to 31.5 °C and the minimum temperature fluctuates from 18.2 °C to 21.1 °C. The variation of the thermal amplitude is from 11.9 °C to 14.4 °C. The mean relative humidity ranges from 72.8% in November to 88% in July, annual precipitation is 956,7mm, it was observed that the annual rate of relative humidity follows the annual distribution of precipitation, because precipitation is the process of feeding natural sources of water vapor and moisture. Total insolation ranged from 134.8 to 240.2 hours and its annual average is 2,361.7 hours. The annual evaporation is 1292.4 mm and the annual evapotranspiration is 1616.8 mm, the annual wind intensity is 2.40 ms-1, with an annual cloud coverage of 0.81 tenths. The computation of the water balance for the CAD, 100 mm aiming at reducing energy and water consumption, reducing the time of use of the water pump used in irrigation.